Perancangan Sistem Informasi Toserba Tasya - Alfiano Tubagus Mukti Nugraha; Elly Halimatusadiah (Bandung Conference Series: Accountancy, 2024)
Abstract. This study aims to design a more effective and efficient information system for Toserba Tasya using the FAST (Framework for Application System Technique) method. By conducting an in-depth analysis of the currently used information system, this research identifies several weaknesses that need solutions to improve operational performance. The proposed information system design includes key elements such as a clear organizational structure, standardized documentation, daily sales reports, and monthly profit and loss statements. A well-defined organizational structure is expected to clarify responsibilities and communication flow, while standardized documents will streamline work processes. Daily sales reports and monthly profit and loss statements will provide better insights into financial performance and aid in decision-making. With the implementation of this design, it is hoped that Toserba Tasya will achieve significant improvements in operational efficiency and effectiveness, enhance internal processes, and improve customer service. Abstrak. Penelitian ini bertujuan merancang sistem informasi yang lebih efektif dan efisien untuk Toserba Tasya dengan menggunakan metode FAST (Framework for Application System Technique). Melalui analisis mendalam terhadap sistem informasi yang saat ini digunakan, penelitian ini mengidentifikasi beberapa kelemahan yang memerlukan solusi untuk meningkatkan kinerja operasional. Dalam rancangan sistem informasi yang diusulkan, terdapat elemen-elemen penting seperti struktur organisasi yang jelas, penyusunan dokumen standar, serta laporan penjualan harian dan laporan laba rugi bulanan. Struktur organisasi yang terdefinisi dengan baik diharapkan dapat memperjelas tanggung jawab dan alur komunikasi, sementara dokumen standar akan mempermudah proses kerja. Laporan penjualan harian dan laporan laba rugi bulanan akan memberikan wawasan yang lebih baik tentang kinerja keuangan dan membantu dalam pengambilan keputusan. Dengan implementasi rancangan ini, diharapkan Toserba Tasya dapat mencapai peningkatan efisiensi dan efektivitas operasional yang signifikan, memperbaiki proses internal, dan meningkatkan pelayanan kepada pelanggan.